2018
DOI: 10.1038/s41467-018-03147-6
|View full text |Cite
|
Sign up to set email alerts
|

Host defense against oral microbiota by bone-damaging T cells

Abstract: The immune system evolved to efficiently eradicate invading bacteria and terminate inflammation through balancing inflammatory and regulatory T-cell responses. In autoimmune arthritis, pathogenic TH17 cells induce bone destruction and autoimmune inflammation. However, whether a beneficial function of T-cell-induced bone damage exists is unclear. Here, we show that bone-damaging T cells have a critical function in the eradication of bacteria in a mouse model of periodontitis, which is the most common infectious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
303
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(318 citation statements)
references
References 62 publications
13
303
1
1
Order By: Relevance
“…To determine the role of SH3BP2 in the pathoetiology of periodontitis, a mouse ligature‐induced periodontitis model was applied to the SH3BP2 knockout mice ( Sh3bp2 −/− ), where an increased oral bacterial load due to accumulation of commensal bacteria within the silk ligature is responsible for periodontal inflammation and subsequent alveolar bone resorption . This ligature model has been widely used to study the molecular mechanisms of periodontitis . To confirm that ligature‐induced periodontitis is dependent on bacterial accumulation surrounding a ligated tooth, we treated a group of 10‐week‐old wild‐type mice with an antibiotic cocktail (ampicillin, vancomycin, kanamycin, metronidazole) in drinking water from 5 days before ligature placement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the role of SH3BP2 in the pathoetiology of periodontitis, a mouse ligature‐induced periodontitis model was applied to the SH3BP2 knockout mice ( Sh3bp2 −/− ), where an increased oral bacterial load due to accumulation of commensal bacteria within the silk ligature is responsible for periodontal inflammation and subsequent alveolar bone resorption . This ligature model has been widely used to study the molecular mechanisms of periodontitis . To confirm that ligature‐induced periodontitis is dependent on bacterial accumulation surrounding a ligated tooth, we treated a group of 10‐week‐old wild‐type mice with an antibiotic cocktail (ampicillin, vancomycin, kanamycin, metronidazole) in drinking water from 5 days before ligature placement.…”
Section: Resultsmentioning
confidence: 99%
“…The SYK inhibitor treatment may meet the requirements of clinical practice because intragingival injection, which would allow to reduce the dose and frequency of SYK inhibitor administration and lessen the risk for potential adverse events, could be considered as a route for administration in humans. Recent investigations demonstrated that T H 17 cells that produce IL‐17A and IL‐17F are the primary drivers for the pathogenesis of periodontitis in mice and humans . These studies provided mechanistic and genetic justification that inhibition of IL‐17 family members or suppression of T H 17 cell development may be a plausible therapeutic option for treatment of alveolar bone resorption in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar strategy revealed that RANKL produced by osteocytes is critical for inflammatory osteolysis in a periodontitis model (Graves et al., ). Interestingly, RANKL produced by T cells only has a minor role, and that RANKL produced by B cells has even no relevance in this respect (Tsukasaki et al., ). These fundamental discoveries provide insights into how RANKL produced by osteocytes is linked to alveolar bone loss.…”
Section: Preamblementioning
confidence: 99%
“…Ligature‐induced periodontitis caused an accumulation of Th17 and neutrophils, while the Tregs were decreased in the oral mucosa. Knockout of IL17A and IL17F inhibited the catabolic changes of periodontitis suggesting a key role of IL17, besides TNFα and IL1, driving inflammatory osteolysis (Tsukasaki et al., ). This is further support for Th17 cells to control the balance between defence and tissue destruction.…”
Section: Preamblementioning
confidence: 99%